Tindakan Tokoh Agama Gampong Terhadap Mitigasi Bencana Banjir (Studi di Gampong Meunasah Dayah Kec. Lhoksukon Kab. Aceh Utara) - Heri Setiawan (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2022)
ABSTRAK Penelitian ini menggambarkan Tindakan Tokoh Agama Dalam Mitigasi Bencana. Tujuan penelitian ini untuk mengetahui tindakan Sosial Tokoh Agama lokal (Ulama) dalam mitigasi bencana banjir di Kecamatan Lhoksukon Kabupaten Aceh Utara. Penelitian ini menggunakan Teori Tindakan Sosial Max Weber. Penelitian ini menggunakan metode kualitatif, pendekatan deskriptif.Hasil penelitian menunjukkan bahwa tokoh agama di Desa Meunasah Dayah tidak memiliki kekuatan dari segi mitigasi bencana, tetapi memiliki kekuatan dari segi profesi selaku tokoh agama yang dipilih oleh masyarakat setempat. Mereka tokoh agama ini memberikan nasehat atau wejangan tentang mitigasi bencana banjir dalam kacamata agama, seperti membuat kajian, zikir bersama, doa tolak bala yang tujuannya disamping mencegah banjir dari segi agama juga memperbaiki perilaku masyarakat. Relasi sosial tokoh agama di Desa Meunasah Dayah yaitu pemberian bantuan sosial. Saat banjir menimpa Desa Meunasah Dayah, Badan Penanggulangan Bencana Daerah bekerjasama dengan Aparatur desa beserta tokoh masyarakat setempat yang di dalamnya ada tokoh agama gampong membagikan paket sembako apabila terjadi banjir di desa tersebut. Kata Kunci :Tokoh Agama, Mitigasi Bencana, BanjirABSTRACT This thesis is entitled "Actions of Religious Leaders in Disaster Mitigation". Thisthesis aims to find out how the social actions taken by local religious leaders (Ulama) in flood disaster mitigation in Lhoksukon District, North Aceh Regency. In addition, to find out the relationship of social actions carried out by localreligious leaders (Ulama) in flood disaster mitigation in Lhoksukon District, North Aceh Regency. In this study the author suseda qualitative method. The selection of subjects or informants in this study using purposive sampling. There are 2 categories of informants taken, namely key informants and additional informants. Methods of data collection using observation, interviews and documentation. Theresults showed that religious leaders in Meunasah Dayah Village did not have thestrength in terms of disaster mitigation, but they had strength in terms of theirprofession as religious leaders who were chosen by the community or the imam /Tengku in the village. These religious figures are only limited to providing adviceor advice on mitigating flood disasters in a religious perspective, such as makingstudies, joint dhikr, prayers to reject reinforcements whose purpose is besides preventing flooding from a religious perspective, andim proving community behavior. The social relations of religious leaders in Meunasah Dayah Village arelike the provision of social assistance. At the time of the flood that hit MeunasahDayah Village, the Regional Disaster Management Agency in collaboration withvillage officials and local community leaders in which there were village religious leaders distributed food packages incaseof floodingin the village. Keywords : Religious Figures, Disaster Mitigation, Floods